2004
DOI: 10.1038/ng1468
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting on distal chromosome 7 in the placenta involves repressive histone methylation independent of DNA methylation

Abstract: Imprinted genes are expressed from only one of the parental chromosomes and are marked epigenetically by DNA methylation and histone modifications. The imprinting center 2 (IC2) on mouse distal chromosome 7 is flanked by several paternally repressed genes, with the more distant ones imprinted exclusively in the placenta. We found that most of these genes lack parent-specific DNA methylation, and genetic ablation of methylation does not lead to loss of their imprinting in the trophoblast (placenta). The silent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
353
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(389 citation statements)
references
References 30 publications
27
353
0
4
Order By: Relevance
“…The antisense Kcnq1ot1 gene appears to be critical for establishing the imprinted profile of the nearby genes (Mancini-Dinardo et al 2006). Recent studies suggest that the Kcnq1ot1 RNA does so by the recruitment of chromatin changes to the imprinted domain, including H3K9 methylation and H3K27 methylation (Lewis et al 2004;Umlauf et al 2004). The Kcnq1ot1 promoter lies within a differentially methylated region of the Kcnq1 gene body and is now known to make up the imprinting center for the BWS domain (Spencer and Lee 2006).…”
Section: Kcnq1 Locusmentioning
confidence: 99%
“…The antisense Kcnq1ot1 gene appears to be critical for establishing the imprinted profile of the nearby genes (Mancini-Dinardo et al 2006). Recent studies suggest that the Kcnq1ot1 RNA does so by the recruitment of chromatin changes to the imprinted domain, including H3K9 methylation and H3K27 methylation (Lewis et al 2004;Umlauf et al 2004). The Kcnq1ot1 promoter lies within a differentially methylated region of the Kcnq1 gene body and is now known to make up the imprinting center for the BWS domain (Spencer and Lee 2006).…”
Section: Kcnq1 Locusmentioning
confidence: 99%
“…The presence of several unmethylated p16 promoter sequences in late passage TERT-transduced HFKs co-cultured with feeders and the observation that p16 expression is induced when these cells are transferred from the co-culture environment to plastic suggest that a subpopulation of cells with functional p16 may exist in the population. Whereas it is possible that other epigenetic mechanisms of gene regulation may be responsible for p16 silencing in the absence of any detectable DNA methylation, such as DNA methylation-independent histone modification (Thiagalingam et al, 2003;Lewis et al, 2004;Zhao et al, 2005), the consistent induction of p16 expression following transfer from the co-culture environment to plastic is highly suggestive of a mixed population of both p16 positive and negative TERT-transduced HFKs. It is reasonable to conclude that upon transfer to the plastic culture condition, those keratinocytes that had retained functional p16 immediately upregulated p16 expression and senesced.…”
Section: Discussionmentioning
confidence: 99%
“…This was first demonstrated at the Ascl2 (also called Mash2) locus: the maternal-specific expression of Ascl2 was maintained in the trophoblast lacking DNMT1 [56]. Later, it was shown that mutations in Dnmt1 do not cause loss of imprinting of the placenta-specific genes in an imprinted cluster on mouse chromosome 7 [57]. Further studies showed that the silent paternal alleles are marked by repressive histone modifications such as H3K9me2, mediated by G9a, and H3K27me3, mediated by the Polycomb repressive complex 2 (PRC2) [57,58].…”
Section: Factors Involved In Imprint Maintenancementioning
confidence: 99%
“…Later, it was shown that mutations in Dnmt1 do not cause loss of imprinting of the placenta-specific genes in an imprinted cluster on mouse chromosome 7 [57]. Further studies showed that the silent paternal alleles are marked by repressive histone modifications such as H3K9me2, mediated by G9a, and H3K27me3, mediated by the Polycomb repressive complex 2 (PRC2) [57,58]. Indeed, mice lacking G9a lose the mono-allelic expression patterns of the placenta-specific genes [59].…”
Section: Factors Involved In Imprint Maintenancementioning
confidence: 99%